The Harvard Business Review manager's handbook : (Harvard Business Review Press, 2017)
Whether you are new to being a boss or are simply looking to stand out from the pack, this is the one primer you need to develop your managerial and leadership skills. Packed with step-by-step advice and wisdom from HBR's management archive, the book provides best practices on topics from building credibility and emotional intelligence to hiring and engaging the best employees, as well as understanding key financial statements and the fundamentals of strategy. Keep this comprehensive guide with you as you grow as a leader and you will have a bigger impact in your organization and on your career.